Pendampingan Pendidik dalam Mengimplementasikan Penguatan Profil Pelajar Pancasila (P5) Tema Suara Demokrasi - Aa Aman Abdur Rahman M Ilyas; Amir Supriatna; Cucu Suwandana; Iis Suryani; Kustati Kustati; Caridin Caridin; Ikka Kartika AF; Agus Mulyanto (Universitas Pahlawan Tuanku Tambusai, 2023)
The independent curriculum is the minister of Education's breakthrough in overcoming the learning vacuum. Character education in the independent curriculum through a project to strengthen the Pancasila student profile is known as P5. In the YPI An-Nur Barudua Malangbong Garut environment, the independent curriculum is still very foreign. The purpose of this assistance is to improve teacher skills in preparing P5 activity modules, organizing the implementation and evaluation and reflection of P5 activities. Assistance activities are divided into three stages. Namely the first stage of delivering material about the independent curriculum and P5. The second stage is guidance on the preparation of the P5 module and its implementation stages. In the third stage, an evaluation and reflection of the mentoring activities is carried out. Based on the evaluation and reflection carried out, this mentoring activity was very useful for teachers in the YPI An-Nur Garut environment. Especially SMP IT An-Nur as the executor of the independent curriculum.